Exploring the connection between playfulness and learning: Making learning memorable in a culturally and economically diverse grade 5 classroom. (March 2022) - Mitton, Jennifer; Murray-Orr, Anne
Highlights: The bulk of the research literature about play and learning is situated in early education and early elementary contexts. The findings of this study show how assessment, learning, and play functioned together in a middle school classroom. Attending to how play was infused into instruction revealed student willingness to engage for the purposes of learning. Abstract: This paper focuses upon the case of one middle school teacher, Jackie. Over the course of an academic year, we explore Jackie's instructional decision making and assessment practices, with a focus on how she infused play into learning and the ways it impacted students. The concept of play and its impact upon learning and engagement is linked to several cognitive, emotional, and social benefits with the bulk of the research literature situated in early childhood education contexts, although some suggest it can take many forms across the continuum of a learner's journey in school. To demonstrate the impact of Jackie's teaching, the findings are represented as found poems showcasing Jackie and her students, showing how a playful approach to learning and assessment was enacted in Jackie's classroom, creating conditions for students to engage in problem solving, analyze/critique ideas, suggest hypothetical thoughts, ask questions, and attempt new skills. Implications of attending to how Jackie infused play into daily decision-making related to instruction, assessment and interpretation of curriculum include enabling us to understand more about how a playful pedagogy can support middle school students' willingness to engage and persist with learning.